Telemak Khachatryan - Babayan, Frina (ARAMAZD: Armenian Journal of Near Eastern Studies, 2020)
Telemak Khachatryan is one of the most renowned Armenian archaeologists of the 20th century, whose works became indispensable for numerous authors engaged in the research of both Armenian and South Caucasian archaeology.